La politización del pasado: contexto y organización de los festejos de la Independencia de México (2006-2009) - César Iván Vilchis Ortega; Gina Catherine León Cabrera (Caravelle)
This article provides a view on the tensions and political quarrels which emerged around the organization of the festivities celebrating the Indepence Bicentenary in 2010, identifying political practices and transformations of the National Holiday. Therefore, we restored the Organizing National Comission’s organization and the conflicts that appeared because of its institutionalisation within the polarised social context during the last part of Vicente Fox’s six-year term and the beginning of Felipe Calderón’s mandate.